2016
DOI: 10.12955/cbup.v4.736
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Methods of Marketing Management of Luxury Brands for Example Gucci's Collaboration With the Fiat Company

Abstract: Branding is a basic and necessary tool in marketing. Recognizable brands develop international trade, cooperation, and exchange of goods. Of late, luxury brands have entered a new level of marketing and customer interaction, whereas, previously, brands specializing in one sector of the economy, generally ignored others. Gucci is a luxury brand that has recently teamed up with FIAT, a company with a completely different profile to that of manufacturing in the apparel industry. The aim of this study was to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Through this research, it was found that there was a correlation between company's brand image/recognition and company's revenue. This suggests a fact that the more well-known a brand is, the more revenue a company will make (Kasztalska, 2016).…”
Section: Collaborationmentioning
confidence: 99%
“…Through this research, it was found that there was a correlation between company's brand image/recognition and company's revenue. This suggests a fact that the more well-known a brand is, the more revenue a company will make (Kasztalska, 2016).…”
Section: Collaborationmentioning
confidence: 99%